Pengaruh Atribut Produk Terhadap Minat Beli Makanan Ringan Tradisional Pada Remaja Di Perkotaan Sumatera Barat - Susi Evanita; Okki Trinanda (Universitas Negeri Padang, 2017)
This study aims to analyze the effect of West Sumatera’s traditional food product attributes towards teenager’s buying interest in urban cities in West Sumatera. The population of this study are all teenagers in urban cities in West Sumatra who have ever consumed West Sumatera’s traditional food. The sample size was set by 450 respondents by using R.L Gay term, but after verification, eventually the number of samples that can be collected was only 417 students. The data was analysed with linear regression analysis. Hypothesis testing was performed at α = 0.05. The result indicate that The product attributes of West Sumatera’s traditional food has significant influence towards teenagers buying interest in urban cities of ​​West Sumatera.